Bullying Behavior and Social Interaction Ability of School-age Children in Tambangan Public Elementary School 02 Mijen Semarang - Tri Sakti Widyaningsih; Rizki Amalia; Tamrin Tamrin (Alliance oh Health Activists (AloHA), 2019)
Background: Bullying is an aggressive and negative behavior of a person or a group which abuse imbalance power and it is done repeatedly. It aims to hurt the victim by mentally or physically. This action can affect social interaction of children’s life. The number of bullying action showed that 50% occurred in elementary school. Aim: This research aims to analyze the correlation between bullying behavior and social interaction ability in Tambangan Public Elementary School 02 Mijen Semarang. Methods: This study was conducted using cross-sectional approach. Sample size was 122 students, selected using proportional random sampling. The data were collected using questionnaire, then analyzed using Spearman rank test. Results: The results showed that bullying case in elementary school showed in the medium level with the percentage of 54.1% (66 students), medium social interaction with the percentage of 63.1% (77 students). The p-value was 0,000; with the rho of -0.407. Conclusion: There was a correlation between bullying behavior and the social interaction ability of school-age children in Tambangan Public Elementary School 02 Mijen Semarang. Suggestion: Giving stimulus to the school-age children by using assertive communication is expected to prevent bullying action around them. Keywords: bullying; social interaction; school-age children